Rational design of coral ball-like MoS2/N-doped carbon nanohybrids via atomic interface engineering for effective sodium/potassium storage. Issue 39 (20th September 2022) - Sun, Junwei; Jiao, Shilong; Jing, Laiying; Lian, Gang; Cui, Deliang; Wang, Qilong
Abstract : Coral ball-like MoS2 /N–C nanohybrids were designed and prepared purposely by a wet-chemistry approach with subsequent annealing as superior electrode materials for SIBs and PIBs. Abstract : MoS2 with a graphite-like layered structure has been regarded as a promising electrode for sodium-ion batteries (SIBs)/potassium-ion batteries (PIBs) due to its high theoretical capacity. Unfortunately, the poor intrinsic electrical conductivity and limited interlayer distance of MoS2 result in unsatisfactory electrochemical performance of SIBs and PIBs, which greatly restrict its further development. Herein, coral ball-like MoS2 /N–C nanohybrids have been designed and prepared purposely as electrode materials for SIBs and PIBs. The alternate intercalation of N-doped porous carbon (N–C) leads to ultrathin MoS2 nanosheets with an expanded interlayer spacing of MoS2 (0.98 nm), which can endow the facilitative ion diffusion and accommodate the tremendous volume variation. In addition, the MoS2 chemically bonded with N–C could not only greatly enhance the electrical conductivity and facilitate the electron transport, but also maintain the structural stability of the electrode. As expected, when used as an electrode for SIBs, the MoS2 /N–C electrode achieves a remarkable long-term lifespan (222 mA h g −1 at 5 A g −1 after 1000 cycles). In addition, it also displays an enhanced cycling life (175 mA h g −1 at 2 A g −1 after 500 cycles) for PIBs.